Channel estimation for millimeter-wave Very-Large MIMO systems - Araújo, Daniel Costa (2014)
We present an efficient pilot-assisted technique for downlink channel estimation in Very Large MIMO (VL-MIMO) systems operating in a 60 GHz indoor channel. Our estimator exploits the inherent sparsity of the channel and requires quite low pilot overhead. It is based on a coarse estimation stage that capitalizes on compressed sensing, followed by a refinement stage to find the transmit/receive spatial frequencies. Considering a ray-tracing channel model, the system throughput is evaluated from computer simulations by considering different beamforming schemes designed from the estimated channel. Our results show that the proposed channel estimator performs quite well with very low pilot overhead.